The Representation of Postcolonial Nigeria through Habila’s My Uncle Ezekiel’s Protagonist: A Psychoanalytical Study - Boukhalkhal, Yassmine; Selt, Affaf Djihad (Faculty of Letters and Foreign Languages Department of English, 2018)
,My Uncle Ezekiel, through his psychology. In fact, Frantz Fanon is a leading figure in analyzing the psychology of the colonial discourse which, in the context of the story, reflects the situation of post colonial Nigeria. The author describes Ezekiel when he is young as being full of promise, just the British colonialism. Prior to that, Britain sent Christian missionaries promising locals to bring them civilization. In the context of the story, Ezekiel, who was full of promise, reaches a regrettable stage because of drinking. Nevertheless, what kills him in the end is the cold. Thus, the impact of the drink and cold on Ezekiel simulates, respectively, the impact of religion and colonialism on Nigeria and Nigerians. As a result, the Fanonian study aims at scrutinizing the impact of the drink on the psychology of Ezekiel, which can be narrowed down into three concepts, alienation, ambivalence and assimilation. Accordingly, the study is made to be able to figure out the impact of religion as well as the British colonialism on Nigeria and Nigerians